Factors Influencing the Use of Social Media as Main Communication Channel: A Study among the Digital Immigrant Employees of Genting Malaysia Berhad. - Tan, Nicco Joselito Lopez (2018)
Genting Malaysia Berhad (GENM) is the largest integrated resort operator in Malaysia and is exploring the viability of using social media as a primary channel for communication and collaboration among its employees. Currently, GENM employees are already using social media but in an unofficial capacity using different social media sites. GENM management is interested to find out what caused the adoption in order to ensure successful implementation of an official enterprise wide social media tool within the organization. Additionally, GENM is also concerned on the adoption ability of older employees as there is a perception that these employees are more technologically challenged than the younger employees. This research then extended the use of the Unified Theory of Acceptance and Use of Technology (UTAUT) to explain the factors contributing to the adoption and use of social media in GENM focusing on the older workers. In this research, older workers are referred as digital immigrants. The design adopted by this research is quantitative and data were collected from 243 respondents listed as GENM employees and categorically qualified as digital immigrants. It is found that social influence is the strongest predictor with a regression estimate of 0.592 followed by performance expectancy with regression estimate of 0.388 of behavioral intention in using social media in GENM. While effort expectancy and facilitating conditions had an insignificant effect with p-value greater than 0.05. Overall, the study’s empirical results confirmed the theoretical model by predicting 73.3% of the behavioral intention to use social media in GENM.